Product counting system / Mustapa Epit and Mohd. Rodzi Ismail - Epit, Mustapa; Ismail, Mohd. Rodzi (1991)
Our project entitle "Product Counting System" is designed for industrial purposes that counting the number of products. The system can count from 0000 to 9999. The model of the system is shown in figure 1.0 . It consists of -two major parts are: Electronic circuit and Pneumatic circuit. The model that we designed needs the knowledge of pneumatic and electronic. In doing this project, many things have to "be taken into consideration. A lot of researchs. have to "be carried out. Discussions and meetings have to held frequently to solve designing problem that arises. We hope this report will "be useful to those interested to knot; about the system.